(untitled) (Pesquisa Odontológica Brasileira, 2002)
The effect of daily mouthrinses on dental plaque accumulation and on salivary mutans streptococci was investigated in 200 children. The utilized solutions were: a placebo solution composed of mentholated deionized water (group I); 0.12% chlorhexidine gluconate associated to 0.05% sodium fluoride (group II); 0.2% chlorhexidine digluconate (group III), and 0.5% stevioside mixed with 0.05% sodium fluoride, with pH 3.4 (group IV). In order to verify the effect on plaque formation, the accumulation of plaque was assessed by means of the Löe12 index, at the beginning and at the end of the experiment, whereas the quantification of cariogenic streptococci was accomplished on three saliva samples collected at 3 different moments: before the first mouthrinse, 24 hours after the first mouthrinse and 1 week after the last mouthrinse. The mouthrinsing routine was carried out on a daily basis during 4 weeks. Five milliliters of solution were rinsed during 1 minute. The results revealed 4.10, 26.75, 41.20, and 5.91% of reduction in plaque accumulation for groups I, II, III, and IV, respectively. Comparisons between the groups as to plaque reduction revealed that groups II and III were significantly different from groups I (control) and IV (p < 0.05), but did not differ from each other. The solution utilized by group III was the least accepted by children and, as the solution utilized by group II, caused mild dental pigmentation. There were no statistically significant differences as to the levels of mutans streptococci, probably due to the low initial levels observed in each one of the four groups.